Eosinophilic pustular folliculitis. Report of a case and revision of the literature. - Caprari, E.; Bassissi, P.; Allegra, F. (European Journal of Pediatric Dermatology, 2018)
In this article, we describe an 11-year-old patient with pustular and papulopustular follicular lesions on the trunk and limbs. The lesions have been present for about 3 months with a fluctuating course characterized by exacerbations in concomitance with crises of bronchospasm and sporadic remissions. The histologic examination has suggested the diagnosis of eosinophilic pustular folliculitis or Ofuji’s disease. The patient has been treated with systemic steroids, which have determined the complete resolution of the disease.